Analisis Kinerja Sumber Daya Manusia di bidang Jaringan - sri Hariyati Fitriasih, Sri Siswanti (STMIK Sinar Nusantara, 2011)
Performance evaluation of human resources needed as a benchmark employee in good condition are positively correlated with performance. This research material by taking data at CV. Solo Support Network (Networking: Internet Service Provider). Evaluation tool using two-dimensional types, namely: stress data and human resources data and processed in a statistically weighted average (interval measurement scale) and shown in the graph. The results of processing the data are analyzed, so that the obtained results of the evaluation of each employee whether kesetresan levels can affect the performance of employees.Keyword :analysis, evaluation, human resources